Global Financial Tightening Conditions and Foreign Exchange Volatility in Kenya - Caspah Lidiema; Twisha Chakraborty Adhikary (European Scientific Journal, ESJ, 2026)
Emerging-market economies like Kenya are experiencing heightened foreign-exchange (FX) volatility due to ongoing global financial-tightening measures that integrate them into a dysfunctional global economic system yet theoretical models diverge on transmission mechanisms. The Conventional Mundell-Fleming model views flexible rates as shock absorbers, while post-Keynesian-structuralist theory warns of endogenous amplification via balance-sheet fragilities. This study tests these competing frameworks using DCC-GARCH on monthly data (Jan 2004- June 2025) for Kenya's shilling, modeling interactions between US Fed rates (FED), global liquidity (GLI), CBK policy rate (CBR), Foreign exchange reserves, remittances, and global risk factors. Results confirm strong persistence in FX volatility driven by FED tightening and global risk, with significant DCC correlations rejecting transitory absorption. Domestic Monetary policy proxied by Central Bank Rate (CBR) exhibits weak shock response despite high persistence, while FED/CBR and GLI/CBR interactions show procyclical leverage effects validating Köhler's Minskyan cycles over symmetric Mundell-Fleming adjustment. These findings advance the emerging market theoretisation by demonstrating how global financial tightening triggers contractionary balance-sheet channels in debt-dependent economies, limiting domestic monetary policy autonomy. Kenya should prioritize macroprudential buffers alongside reserves accumulation over sole rate reliance to mitigate future US-led volatility spillovers.